Managing obstetric emergencies and trauma : the MOET course manual - Paterson-Brown, Sara; Howell, Charlotte (Cambridge : Cambridge University Press, 2014)
Obstetric emergencies are unplanned and often unanticipated. Management requires a clear understanding of the life-saving and damage-limiting treatments that can be implemented. This manual covers life-threatening emergencies of pregnancy in a systematic and comprehensive way, teaching the skills and procedures needed to save the mother and fetus. Essential anatomical, physiological and pathological information is presented and clinically applied, and treatment algorithms give clear, step-by-step management advice. This easy-to-read, practical handbook is recommended reading prior to the Managing Obstetric Emergencies and Trauma (MOET) course, providing structured preparation and revision, and this updated revision of the third edition reflects the very latest practice and advice from the Advanced Life Support Group. Trainee obstetricians, midwives and anaesthetists will find this invaluable in developing their ability and confidence when facing emergencies, and a useful resource for advanced exams. No obstetric clinician should be without it.
Title from publisher's bibliographic system (viewed on 06 Jun 2016).
Keywords: Obstetrical emergencies; Pregnancy -- Complications; Gynecologic emergencies